Integrating 21st Century Character Education in Mathematics Learning for Elementary School Students - Desti Rahayu; Sabar Narimo; Achmad Fathoni (Academia Edu Cendekia Indonesia (AEDUCIA), 2025)
Background: The integration of 21st-century character education in mathematics learning is crucial for developing students' academic and personal skills, ensuring they are prepared for future challenges. Objective: This study aims to describe the implementation of 21st-century character education in mathematics learning for elementary school students, specifically focusing on how these values are integrated into the curriculum at SD Negeri 2 Sukorejo, Klaten. Method: The research used a descriptive qualitative approach, involving the principal, teachers, and students as subjects. Data was collected through observation, interviews, and documentation, with validity ensured through source triangulation. Data analysis followed the steps of collection, reduction, presentation, and conclusion drawing. Results: The study found that the implementation of 21st-century character education at SD Negeri 2 Sukorejo was effectively integrated into the Learning Implementation Plan (RPP). This integration helped promote essential character values such as responsibility, critical thinking, and collaboration within mathematics learning. Conclusion: The implementation of 21st-century character education at SD Negeri 2 Sukorejo demonstrates that integrating character values into mathematics lessons can enhance students' academic skills and moral development. This approach contributes to preparing students for the challenges of the modern world. Contribution: The findings of this study provide valuable scientific information for teachers on how to integrate 21st-century character education into mathematics learning for elementary school students. It serves as a useful reference for educators seeking to foster character development alongside academic achievement.